Influence of cryopreservation on perinatal outcome after blastocyst‐ vs cleavage‐stage embryo transfer: systematic review and meta‐analysis. (3rd January 2018) - Alviggi, C.; Conforti, A.; Carbone, I. F.; Borrelli, R.; de Placido, G.; Guerriero, S.
ABSTRACT: Objective: To compare the perinatal outcomes of singleton pregnancies resulting from blastocyst‐ vs cleavage‐stage embryo transfer and to assess whether they differ between fresh and frozen embryo transfer cycles. Methods: A systematic review of the literature was carried out using the Scopus, MEDLINE and ISI Web of Science databases with no time restriction. We included only peer‐reviewed articles involving humans, in which perinatal outcomes of singleton pregnancies after blastocyst‐stage embryo transfer were compared with those after cleavage‐stage embryo transfer. Primary outcomes were preterm birth before 37 weeks and low birth weight (< 2500 g). Secondary outcomes were very preterm birth before 32 weeks, very low birth weight (< 1500 g), small‐for‐gestational‐age (SGA), large‐for‐gestational‐age (LGA), perinatal mortality and congenital anomaly. A meta‐analysis was performed using a random‐effects model. Three subgroups were evaluated: fresh only, frozen only and fresh plus frozen embryo transfer cycles. Results: From a total of 3928 articles identified, 14 were selected for qualitative/quantitative analysis. Significantly higher incidences of preterm birth < 37 weeks (11 studies, n  = 106 629 participants; risk ratio (RR), 1.15 (95% CI, 1.05 − 1.25); P  = 0.002) and very preterm birth < 32 weeks (seven studies, n  = 103 742; RR, 1.16 (95% CI, 1.02–1.31); P  = 0.03) were observed after blastocyst‐ than after cleavage‐stage embryo transfer in fresh cycles. However, the risk of preterm and very preterm birth was similar after blastocyst‐ and cleavage‐stage transfers in frozen and fresh plus frozen cycles. Overall effect size analysis revealed fewer SGA deliveries after blastocyst‐ compared with cleavage‐stage transfer in fresh cycles but a similar number in frozen cycles. Conversely, more LGA deliveries were observed after blastocyst‐ compared with cleavage‐stage transfer in frozen cycles (two studies, n  = 39 044; RR, 1.18 (95% CI, 1.09–1.27); P  < 0.0001) and no differences between the two groups in fresh cycles (four studies, n  = 42 982; RR, 1.14 (95% CI, 0.97–1.35); P  = 0.11). There were no differences with respect to low birth weight, very low birth weight or congenital anomalies between blastocyst‐ and cleavage‐stage transfers irrespective of the cryopreservation method employed. Only one study reported a higher incidence of perinatal mortality after blastocyst‐ vs cleavage‐stage embryo transfer in frozen cycles, while no differences were found in fresh cycles. Conclusions: Our results suggest that cryopreservation of embryos can influence outcome of pregnancy conceived following blastocyst‐ vs cleavage‐stage embryo transfer in terms of preterm birth, very preterm birth, LGA, SGA and perinatal mortality. Caution should be exercised in interpreting these findings given the low level of evidence and wide heterogeneity of the studies. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.